2019
DOI: 10.22437/jiiip.v22i2.8351
|View full text |Cite
|
Sign up to set email alerts
|

Inventarisasi Emisi Gas Rumah Kaca (CH4 dan N2O) Dari Sektor Peternakan Sapi Dengan Metode Tier-1 IPCC di Kabupaten Muaro Jambi

Abstract: Gas rumah kaca (GRK) dalam bentuk CH4 dan N2O  memberikan kontribusi terhadap pemanasan global. Sektor pertanian menyumbang 10-12% dari total GRK antropogenik dari gas CH4 dan N2O. Sedangkan sektor peternakan menyumbang sekitar 18-51% GRK antropogenik. Penelitian bertujuan untuk menganalisis beban emisi gas CH4 dan N2O bersumber dari Peternakan terhadap GRK Di Kabupaten Muara Jambi yang diestimasi dengan menggunakan metode Tier-1 IPCC. Pada metode ini data yang diperlukan adalah populasi ternak dalam satu tahu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Therefore, it is crucial for Jambi Province to develop effective strategies to manage CH4 emissions, especially from dairy cattle, to mitigate the impact on the environment. Such strategies should aim to reduce the amount of CH4 produced by dairy cattle while increasing their productivity and overall health (Syarifuddin et al, 2019). This condition will be give negative impact on ozone.…”
Section: Provincial Contribution Of Ch4 Emissionsmentioning
confidence: 99%
“…Therefore, it is crucial for Jambi Province to develop effective strategies to manage CH4 emissions, especially from dairy cattle, to mitigate the impact on the environment. Such strategies should aim to reduce the amount of CH4 produced by dairy cattle while increasing their productivity and overall health (Syarifuddin et al, 2019). This condition will be give negative impact on ozone.…”
Section: Provincial Contribution Of Ch4 Emissionsmentioning
confidence: 99%
“…The emissions in [12] with TIU for Livestock Breeding-Green Forage Jember is the same as the emissions of 5 mature dairy cows in TIU Jember, which is 10.800 kilotons of CO2-eq /year or 2.150 kilotons of CO2-eq /year /head. The previous research [4] stated that the emission of CH4 in livestock from EnF is influenced by livestock type and population.…”
Section: Methane Emission (Ch4)mentioning
confidence: 99%
“…The livestock subsector was based on two main activities, namely enteric fermentation (EnF) and dung management (DM), and potentially emitted gases of CH4 and N2O. The gas emission of CH4 and N2O was based on [4], which showed that CH4 emissions amounted to 1.1466 Gg per year, and N2O emissions amounted to 535.73 kg per year. Methane gas from enteric fermentation occurs during digestion when microorganisms in livestock, particularly ruminants, break down carbohydrates [5].…”
Section: Introductionmentioning
confidence: 99%
“…Data were taken from 15 farmer groups from 15 districts and 6 households of rice farmers assisted by Tangguh LNG CSR in Teluk Bintuni Regency. The calculation method uses IPCC 2006 Tier 2[53,54]. The correction factor used in calculating the Bintuni GHG is adjusted based on land area, soil type, type of fertilizer, type of irrigation used.The calculated GHG emissions from the agricultural and plantation sectors are from rice planting activities, fertilizer use, and soil management.…”
mentioning
confidence: 99%